Isolation And Characterization of Physicochemical Properties of Mucilago Gedi Leaf (Abelmoschus manihot L. Medik) - Elvie Rifke Rindengan; Marline Abdassah; Anis Yohana Chaerunisaa (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
The aim of this research was to isolation of mucilage from gedi leaf (Abelmoschus manihot L. Medik) and characterized physicochemical properties. The isolation result was yellowish brown powder that swelling and dissolves slowly in water, but does not dissolve in ethanol, methanol, acetone and ether. The yield is 1.33%. Swelling index value 100% and viscosity 28 ± 2.65 mpas, pH 7.1. Proximate analysis showed 10.46% water content, 38.80% ash, 14.66% protein, 0.69% fat, 35.38% carbohydrate Water holding capacity (WHC) and  oil holding capacity (OHC) of musilago are respectively 4.23 ± 0.18 and 0.65 ± 0.14. Viscosity, Swelling index, WHC and OHC mucilage gedi leaf  may be considered as pharmaceutical excipients.Keywords: Mucilage, Abelmoschus manihot, swelling, viscosity